Factors Influencing Islamic Education Management; Educators, Curriculum, Work Culture - Kusminin, Kusminin (International Journal of Advanced Multidisciplinary, 2023)
In carrying out Islamic education management, it is important to pay attention to and manage these factors. educators , curriculum and work culture. Qualified educators have a very important role in the management of Islamic education. Curriculum plays an important role in the management of Islamic education. Factors that influence the management of Islamic education through the curriculum include: relevance, continuity, adaptability, and Islamic integrity. The work culture that is built in the Islamic education environment also has a major influence on educational management. Several factors influence the management of Islamic education through work culture, including: Cooperation, Leadership, work ethic, and professional ethics.